How could 20-minute neighbourhoods impact health and health inequalities? A policy scoping review - Roxana Pollack; Jonathan R Olsen; Alison Heppenstall; Andreas Hoehn; Jennifer Boyd; Vicki Ponce Hardy; Jennifer Littlejohn; Amy Stevenson; Richard Mitchell; Petra Meier; Jonathan Stokes (BMC Public Health)
Abstract Background ‘Twenty-minute neighbourhoods’ (or variations, such as 15-minute cities) are receiving increasing policy attention with anticipated impacts on population health (inequalities) outcomes alongside sustainability improvements. Yet, factors contributing to possible health impacts are not well understood. This scoping review aimed to identify proposed and evidenced pathways to health (inequality) outcomes from international policy plans. Methods We first identified relevant academic literature, searching Scopus, (Ovid) Medline and Embase databases. A second search aimed to identify local or national planning or policy documents on government websites and related organisations. We followed a snowball search strategy to retrieve examples identified from the academic literature search and from the C40 cities network. These policy documents were our primary target for extraction, and we extracted and analysed by individual place. Pathways to health and health inequality outcomes identified in these documents were inductively coded thematically. We used Sankey diagrams to visually aggregate the thematic codes for each place relating to pathways to health outcomes and social determinants (mechanisms). Results In total, 36 places across 17 countries were included, described across 96 academic articles, policy plans and reports. While different health improvement outcomes were included as a goal in nearly all policy plans, most frequently references were to health in general rather than specific health outcomes. Pathways to health were discussed in numerous policy plans across three overarching themes: proximity, place redesign, and environmental action. Proximity pathways were most frequently outlined as the means to achieve health outcomes, with active travel acting through increased physical activity/reduced obesity as the most frequent individual pathway. However, few plans specified what would actually be implemented in practice to achieve the increased proximity to services. Health inequalities were only mentioned by six places specifically, although nearly half of all places mentioned broader inequality aims (e.g., poverty reduction). Possible unintended consequences to health inequalities also received some attention, for example through displacement of residents. Discussion Pathways to assumed health (inequality) outcomes require better specification and evidence. Health inequalities are particularly under-explored, and scenario modelling might provide a means to explore the dynamic aspects necessary to examine these important outcomes pre-implementation.